Pengaruh Perputaran Kas, Perputaran Piutang dan Leverage (DER) Terhadap Profitabilitas (ROA) Pada Perusahaan Pertambangan yang Terdaftar di BEI 2016-2018 - Elli Frisca Napitupulu; Rendi Andika Ginting; Rini Monika Sinurat; Yemima Nadeak; Friska Darnawati Sitorus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In a company always expects high profitability, but that will not be achieved if the operational process does not run well, meaning that the company certainly requires a lot of capital in managing its business. With this we as researchers want to discuss and analyze how